Angioarchitecture of spider veins - Wienert, V.; Simon, H. P.; Böhler, U. (Phlebologie, 2006)
Knowledge of the anatomy of spider veins is scant and contradictory. The authors therefore decided to investigate the angioarchitecture of these lesions, i.e. the anatomy, interconnections, and morphological characteristics of the cutaneous vessels and capillaries that comprise them. Material and methods: A highly polymerising plastic was injected into the vascular system of skin-muscle tissue blocks so as to produce true-to-scale casts (corrosion casts) of the angioarchitecture of spider veins. In 35 skin-muscle tissue blocks obtained post mortem a total of 28 spider veins were found. Corrosion casts of these were examined by scanning electron microscopy with particular regard to their connections with larger veins. Results: All the spider veins examined showed the typical polygonal pattern of endothelial cell nuclear imprints. The subpapillary vascular plexus showed incompetent microvenous valves. A statistically significant difference was found between the diameter of spider veins of red and blue appearance (0.227 mm and 0.435 mm, respectively; p<0.001). Feeder veins were only found in the case of stellate and fan-shaped spider veins. Conclusions: Spider veins are pathological venous changes in the subpapillary vascular plexus. Incompetent microvenous valves may play a role in their formation. In certain clinical situations sclerotherapy of spider veins may fail to achieve a lasting cure, since the feeder veins that drain the capillaries cannot be sclerosed.
Keywords: Spider veins; angioarchitecture; corrosion casts; scanning electron microscopy